Factors Influencing Carbon Emission Disclosure - Desiana Desiana; Ulfa Luthfia Nanda; Iwan Hermansyah (Value : Jurnal Manajemen dan Akuntansi, 2026)
The issue of global warming has captured the world’s attention; the rise in carbon emissions released by industry and motor vehicles is believed to be the cause. The world has committed to reducing the greenhouse gas effect through the Kyoto Protocol, an international agreement adopted to reduce greenhouse gas emissions and implemented in Kyoto in 1997. This study provides an empirical analysis specifically examining the influence of company growth, the size of the board of commissioners, the presence of female directors, and the size of the board of directors on carbon emissions disclosure among energy companies in emerging markets; whilst similar research has been extensively conducted in developed nations, it remains very limited in emerging markets. The population for this study comprises energy sector companies listed on the Indonesia Stock Exchange for the period 2018–2022 that published annual reports and/or sustainability reports. The sampling technique employed purposive sampling; the total sample comprised 18 energy sector companies with a total of 90 observations meeting the criteria. The analysis utilised multiple linear regression to test the hypotheses. The results of this study indicate that female directors have a significant influence on carbon emissions disclosure, whilst company growth, the size of the board of commissioners, and the size of the board of directors do not influence carbon emissions disclosure.